The need to address the challenge of non- payment of retirement fund contributions: a case for necessary legislative amendments - Maraka, Mokheche Stephen (University of the Witwatersrand, Johannesburg, 2023)
The challenge of the employers’ failure to pay retirement funds contributions to the retirement funds to which their employees are members is prevalent in South Africa. With the current legislative framework, it does not seem like this conduct is subsiding. The Pension Fund Act 24 of 1956 has criminalized the non-payment of contributions, however, the problem persists. In this regard, this research report evaluates the effectiveness of the current legislative framework and criminal sanctions in addressing this challenge, with the aim of making recommendationson how this challenge can be legislatively addressed
A research report Submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report, School of Law, University of the Witwatersrand, Johannesburg 2023
Keywords: Retirement fund; Non-payment; Pension Fund Act 24 of 1956; UCTD; SDG-8: Decent work and economic growth